Thermal behaviour of succinic acid, sodium succinate and its compounds with some bivalent transitions metal ions in dynamic N2 and CO2 atmospheres - Caires, C. F.J. [UNESP]; Lima, L. S. [UNESP]; Carvalho, C. T. [UNESP]; Ionashiro, M. [UNESP] (Ecletica Quimica, 2010)
Thermal stability and thermal decomposition of succinic acid, sodium succinate and its compounds with Mn(II), Fe(II), Co(II), Ni(II), Cu(II) and Zn(II) were investigated employing simultaneous thermogravimetry and differential thermal analysis (TG-DTA) in nitrogen and carbon dioxide atmospheres and TG-FTIR in nitrogen atmosphere. On heating, in both atmospheres the succinic acid melt and evaporate, while for the sodium succinate the thermal decomposition occurs with the formation of sodium carbonate. For the transition metal succinates the final residue up to 1180 ºC in N2 atmosphere was a mixture of metal and metal oxide in no simple stoichiometric relation, except for Zn compound, where the residue was a small quantity of carbonaceous residue. For the CO2 atmosphere the final residue up to 980 ºC was: MnO, Fe3O4, CoO, ZnO and mixtures of Ni, NiO and Cu, Cu2O.
Keywords: Bivalent transitions metals; Succinate; Thermal behavior